Segmentos de anillos corneales intraestromales para el manejo de ectasia de aparición tardía tras queratotomía radiada - Gustavo Ortiz-Morales; Denise Loya-García; Mónica I. Herrera-Rodríguez; Julio C. Hernández-Camarena; Jorge E. Valdez-García (Revista Mexicana de Oftalmología)
Objective: To report the uncommon scenario of post-radial keratotomy (RK) ectasia and the subsequent management with intrastromal corneal ring segments (ICRS). A 50-year-old male with a history of RK 12 years prior presented with a complaint of decreased vision in both eyes. Observations: Initial manifest refraction showed a high hyperopic shift with an uncorrected distance visual acuity (UDVA) of 1.30 logMAR and 1.45 logMAR in OD and OS, respectively. Corneal topography was consistent with post-RK ectasia. ICRS were implanted in both eyes. No intraoperative or post-operative complications were observed. One month postoperatively, UDVA improved to 0.69 logMAR in OD and 0.87 logMAR in OS. Binocular UDVA was 0.47 logMAR. Conclusions: ICRS implantation resulted in an improvement in the topographic parameters, refractive astigmatism, and visual acuity 1 month postoperatively. This case portrays the successful management of the uncommon scenario of post-RK ectasia with ICRS implantation.